1999
DOI: 10.1029/1999jd900397
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Limb Array Etalon Spectrometer observations of tropical cirrus

Abstract: The CLAES Instrument and DataThe instrument and operation have been described in detail by Roche et al. [1993]. In brief, CLAES acquired mediumresolution spectra of infrared thermal emission from the Earth's limb in nine channels ranging from 3.5 to 12.8 /am, corresponding to the altitude range of approximately 10-60 km. The viewing geometry of the 57 ø inclination UARS orbit provides for daily coverage extending from either 34øS to 80øN (north-look) or 34øN to 80øS (south-look), depending on the orientation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 22 publications
2
59
0
Order By: Relevance
“…These large optical depths are larger than gas optical depths and enhance 12.1 mm atmospheric limb view radiances. Previous measurements of 12 mm PSC emission by ISAMS and CLAES [Taylor et al, 1994;Massie et al, 1994] and of subvisible cirrus by CLAES [Mergenthaler et al, 1999] confirm this simple physics.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…These large optical depths are larger than gas optical depths and enhance 12.1 mm atmospheric limb view radiances. Previous measurements of 12 mm PSC emission by ISAMS and CLAES [Taylor et al, 1994;Massie et al, 1994] and of subvisible cirrus by CLAES [Mergenthaler et al, 1999] confirm this simple physics.…”
Section: Introductionsupporting
confidence: 62%
“…Thin cirrus is commonly referred to as ''subvisible'' cirrus, since the human eye, looking upward, cannot detect these optically thin clouds. Cirrus extinctions near the tropopause were measured by CLAES [Mergenthaler et al, 1999] Gille et al, submitted manuscript, 2007) joins the roster of space experiments which can measure clouds in the stratosphere and upper troposphere. HIRDLS is a limb viewing emission experiment with 21 spectral channels in the infrared, spanning the wavelength range from 6.2 to 17.2 mm, and was designed to measure temperature-pressure profiles, the mixing ratios of many gas species (i.e., O 3 , HNO 3 , H 2 O, NO 2 , N 2 O, CH 4 , CFC-11, CFC-12, ClONO 2 , N 2 O 5 ), and cloud/ aerosol extinction profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Here we argue that infrared (IR) limb sounding from space provides an alternative measurement technique of high sensitivity for the detection of optically thin clouds (Mergenthaler et al, 1999;Massie et al, 2007;Griessbach et al, 2014), subvisible cirrus (SVC) defined by the extinction range 2 × 10 −4 -2 × 10 −2 km −1 (Sassen et al, 1989), or the even thinner ultra-thin tropical cirrus (UTTC) Luo et al, 2003). The IR limb sounder detection sensitivity for clouds is in the range of spaceborne lidar measurements (Höpfner et al, 2009;Spang et al, 2012).…”
Section: R Spang Et Al: Satellite Observations Of Cirrus Clouds In mentioning
confidence: 99%
“…Previous studies examining the effects of El Nino on upper tropospheric cirrus have based their results on observations by satellites from space (Wang et al, 1996;Mergenthaler et al, 1999;Sandor et al, 2000;Massie et al, 2000;Cess et al 2001). Massie et al (2000) analysed geographical distributions of aerosol extinction data in the troposphere and stratosphere for 1993-1998 from the Halogen Occultation Experiment (HALOE) and showed that during El Nino conditions of 1997 upper tropospheric cirrus increased over the mid-Pacific and decreased over Indonesia.…”
Section: Introductionmentioning
confidence: 99%